تراسل الوسائط التواصلية "قراءة في صراع الحيوان من خلال الأنظمة التواصلية" - رحيمة, شيتر (قــــــراءات; No 09 (2016): مجلة قراءات, 2019)
يقوم المقال على افتراض مفاده أن الصوت أو الكتابة أو الصورة الرقمية أنساق تواصلية متكاملة، تخفي جوانب غير يسيرة من أغوار النفس البشرية ،وللتأكد من صحة هذا الافتراض عمد المقال إلى ثلاث نماذج تواصلية تنتمي إلى أنظمة  وأزمنة وأمكنة مختلفة باحثة في وهمية  أو يقينية التعالق بينها ،هذه النماذج هي: 1 رسوم على جدران الكهوف (رسمين يمثل أحدهما صورة الصيد، ويمثل الآخر صورة البقرة الباكية ) 2 نماذج من الشعر الجاهلي الذي يغلب عليه طابع المشافهة وقد  المداخلة عل نموذج صراع الحيوان في رحلة الصيد ،وصورة الثكل التي تمثلها البقرة. نماذج لفيديوهات في البراري تمثل صراع الحيوان من أجل البقاء، يركز أحد الفيديوهات على افتراس البقرة وتكالب الأسود عليها، بينما يمثل الفيديو الثاني انتصار الحيوان الضعيف في مواجهة الحيوان المفترس. Abstract This article hypothesizes that the sound, the writing or the digital image are overlapped communicative patterns which hide considerable sides of the human beings’ deep psychology. To verify this hypothesis, the article uses three communicative models which belong to different systems, epochs, and places seeking the uncertainty and certainty of their associations. These models are: 1) Paintings/graphics on caves’ walls (one is of the hunting scene and the other is the one of the tearing cow). 2) Models of the ancient Arabic poetry (Eljahili), which is dominated by orality and the description of the animal fight in a hunting trip, in addition to the image of the widowed cow. 3) Models of videos in wild prairies portraying the animals struggle for survival. One of the videos shows an attack of lions on a cow, while the other video pictures the victory of the weak animal over its preyer.